2011
DOI: 10.5433/2236-6407.2011v2n2p211
|View full text |Cite
|
Sign up to set email alerts
|

Sociometria e habilidades sociais em alunos do ensino médio

Abstract: ResumoEsta pesquisa teve como objetivo verificar as correlações entre habilidades sociais e aceitação entre os pares tanto para a situação de estudar como de sair. Foram avaliados 45 adolescentes de 16 a 18 anos, todos provenientes de uma escola particular de uma cidade do interior do estado de São Paulo. Foi aplicado o Inventário de Habilidades Sociais e o Questionário Sociométrico de forma coletiva aos alunos previamente autorizados. Foram encontradas apenas correlações significativas entre as medidas sociom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
6
1
6

Year Published

2016
2016
2017
2017

Publication Types

Select...
7

Relationship

6
1

Authors

Journals

citations
Cited by 10 publications
(15 citation statements)
references
References 3 publications
2
6
1
6
Order By: Relevance
“…On one hand, this might happen due to the larger variability both of social skills groups and of performance in writing and mathematics in these school years. On the other hand, it strengthens the evidence that a larger group of social skills tends to facilitate learning in different areas, as suggested in other research with this regard (Bartholomeu et al, 2009;Bartholomeu, Montiel, et al, 2011;Del Prette & Del Prette, 2003;Montiel et al, 2011;Stone & La Greca, 1990;Vaughn & Hogan, 1990;Vaughn et al, 1991). Note.…”
supporting
confidence: 57%
See 2 more Smart Citations
“…On one hand, this might happen due to the larger variability both of social skills groups and of performance in writing and mathematics in these school years. On the other hand, it strengthens the evidence that a larger group of social skills tends to facilitate learning in different areas, as suggested in other research with this regard (Bartholomeu et al, 2009;Bartholomeu, Montiel, et al, 2011;Del Prette & Del Prette, 2003;Montiel et al, 2011;Stone & La Greca, 1990;Vaughn & Hogan, 1990;Vaughn et al, 1991). Note.…”
supporting
confidence: 57%
“…Even though some correlations had been low, these results could be refl ected in terms of group cohesion, since social skills consist in some of the characteristics that ensure a better group cohesion mainly based on the decrease of social rejection (Bartholomeu, Carvalho, Silva, Miguel, & Machado, 2011;Bartholomeu, Montiel, et al, 2011;Gifford-Smith & Brownell, 2003). Furthermore, studies have showed that a good group cohesion usually facilitates school performance (Gifford-Smith & Brownell, 2003).…”
Section: Final Considerationsmentioning
confidence: 99%
See 1 more Smart Citation
“…Por outro, fortalece a evidência de que um maior repertório de habilidades sociais tende a facilitar o aprendizado em diferentes áreas como sugerem outras pesquisas neste âmbito (Bartholomeu et al, 2009;Bartholomeu, Montiel, et al, 2011;Del Prette & Del Prette, 2003;Montiel et al, 2011;Stone & La Greca, 1990;Vaughn & Hogan, 1990;Vaughn et al, 1991).…”
Section: Habilidades Sociais E Desempenho Escolar Em Português E Mateunclassified
“…Diferentes estudos enfocando a avaliação pelos colegas também demonstraram que os alunos com menor desempenho escolar são menos aceitos que seus colegas sem essas difi culdades (Bartholomeu, Montiel, & Pessotto, 2011;Stone & La Greca, 1990;Vaughn & Hogan, 1990;Vaughn, McIntosh, & Spencer-Rowe, 1991 (Elliott, Pring, & Bunning, 2002;Gresham, 2009;Swanson & Malone, 1992). Deste modo, Gresham (1992) sugere três hipóteses que podem nortear os estudos entre habilidades sociais e difi culdades escolares: a hipótese causal, na qual os défi cits em habilidades sociais e a incapacidade de aprendizado seriam atribuídos à disfunção do sistema nervoso central; a hipótese da concomitância entre deficiência em habilidades sociais e difi culdades de aprendizado; e a hipótese correlacional, ou seja, uma tendência de parte dos alunos com maiores escores em habilidades sociais apresentarem melhor rendimento escolar.…”
unclassified